Oxygen consumption during concurrent training: influence of intra-session exercise sequence and aerobic exercise modality - Rodrigo Ferrari; Cristine Alberton; Stephanie Pinto; Eduardo Cadore; Ronei Pinto; Luiz Fernando Kruel (Termedia Publishing House, 2018)
To compare the acute effects of different intra-session exercise sequences and aerobic exercise modalities during concurrent training sessions on oxygen consumption (VO 2 ) and energy expenditure (EE) in young women. Eleven young women volunteered to participate in this study and underwent tests of their dynamic strength and a maximal incremental test on both the treadmill and cycle ergometer. Four concurrent training sessions were performed: resistance-running (RRu), resistance-cycling (RC), running-resistance (RuR) and cycling-resistance (CR). The aerobic exercise lasted 30 minutes and was performed at a heart rate equivalent to 95% of the second ventilatory threshold. The resistance exercise lasted approximately 21 minutes and consisted of 4 sets of 10 RM in each exercise. The VO 2 was continuously evaluated through the portable gas analyser. No differences were found in the VO 2 between the intra-session exercise sequence independently of aerobic modality (i.e., RRu vs. RuR, and RC vs. CR), and the sessions with the running aerobic exercise showed greater VO 2 than sessions using cycling aerobic exercise in both exercise sequences (VO 2 aerobic (ml · kg-1 · min-1) - RRu: 27.5; RuR: 27.1; RC: 20.2; CR: 20.8). The present study showed that the intra-session exercise sequence during concurrent training does not influence VO 2 . However, the optimal combination of resistance and aerobic exercise should include running in order to increase VO 2 and optimize EE.